2016
DOI: 10.1177/1740774516669352
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of multimedia informational aids for research on medical practices: Implications for informed consent

Abstract: Background/aims Participant understanding is a key element of informed consent for enrollment in research. However, participants often do not understand the nature, risks, benefits, or design of the studies in which they take part. Research on medical practices, which studies standard interventions rather than new treatments, has the potential to be especially confusing to participants because it is embedded within usual clinical care. Our objective in this randomized study was to compare the ability of a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Animations are a passive medium, in which the flow of information is not controlled by the receiver and this may be a disadvantage from an educational perspective [Tversky, Morrison and Betrancourt, 2002;Yang, 2008]. Only a recent study directly compared comics and animation as medical informational aids, finding that animated videos (or slideshows with voice-over narration) are more effective than comics in explaining medical practices, although both were more effective than text alone [Kraft et al, 2016]. More studies of this kind will be required in order to determine which visual strategies are more effective, on which topics and for which audiences.…”
Section: Metaphoric Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Animations are a passive medium, in which the flow of information is not controlled by the receiver and this may be a disadvantage from an educational perspective [Tversky, Morrison and Betrancourt, 2002;Yang, 2008]. Only a recent study directly compared comics and animation as medical informational aids, finding that animated videos (or slideshows with voice-over narration) are more effective than comics in explaining medical practices, although both were more effective than text alone [Kraft et al, 2016]. More studies of this kind will be required in order to determine which visual strategies are more effective, on which topics and for which audiences.…”
Section: Metaphoric Researchmentioning
confidence: 99%
“…When compared to traditional text-based material, comics appear to significantly improve understanding and recollection of medical conditions [Diamond et al, 2016;Tekle-Haimanot et al, 2016], compliance with medical instructions [Delp and Jones, 1996;Tjiam et al, 2013], promote informed consent [Furuno and Sasajima, 2015;Kraft et al, 2016], facilitate interactions between patients and doctors [Anderson, Wescom and Carlos, 2016] and between patients and their communities [McNicol, 2014;McNicol, 2017], and generally improve community engagement with medical issues [Leung et al, 2014;Wang, Acevedo and Sadler, 2017]. However, the health-related information presented in these comics clearly has a different emotional value than generic scientific knowledge.…”
Section: Current Research On Educational Comicsmentioning
confidence: 99%
“…Many of the attributes of digital platforms, such as dual-channel messaging-coupling audio to video-and use of quizzes to check for understanding, can enhance learning for patients/clients who benefit from taking in new information through multiple means (Kraft et al 2017). Digital platforms can also extend access of services to patients/clients who may otherwise not be able to travel to a medical center.…”
Section: Alternative Service Delivery Modesmentioning
confidence: 99%
“…In our experience, this process enriches the investigation as parents provide a complementary lens in the analysis. In many of our projects, we found that resource parents make invaluable contributions to the development of themes, results, and analysis of results [33]. …”
Section: Historymentioning
confidence: 99%